2019
DOI: 10.1186/s40814-019-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a two-arm feasibility RCT to support postnatal maternal weight management and positive lifestyle behaviour in women from an ethnically diverse inner city population: the SWAN feasibility trial

Abstract: IntroductionA high BMI during and after pregnancy is linked to poor pregnancy outcomes and contributes to long-term maternal obesity, hypertension, and diabetes. Evidence of feasible, effective postnatal interventions is lacking. This randomised controlled trial will assess the feasibility of conducting a future definitive trial to determine effectiveness and cost-effectiveness of lifestyle information and access to Slimming World® (Alfreton, UK) groups for 12 weeks commencing from 8 to 16 weeks postnatally, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Of 10,886 studies screened, 28 studies were included reporting on 17 interventions. Of the 28 studies, nine were study protocols [29][30][31][32][33][34][35][36] and 19 were effectiveness studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (Figure 1). Two interventions were both reported in two different effectiveness studies (N = 4); from one intervention, two studies were published; one on mothers' outcomes 37 and one on their partners 53 ; and from another intervention two studies reported on dietary outcomes 41 and physical activity outcomes separately.…”
Section: Resultsmentioning
confidence: 99%
“…Of 10,886 studies screened, 28 studies were included reporting on 17 interventions. Of the 28 studies, nine were study protocols [29][30][31][32][33][34][35][36] and 19 were effectiveness studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (Figure 1). Two interventions were both reported in two different effectiveness studies (N = 4); from one intervention, two studies were published; one on mothers' outcomes 37 and one on their partners 53 ; and from another intervention two studies reported on dietary outcomes 41 and physical activity outcomes separately.…”
Section: Resultsmentioning
confidence: 99%